Automated 1-2-1 Communication - Araujo, Theo, ....-; ter Hoeven, Claartje, ....-; van Zoonen, Ward, ....- (Amsterdam : SWOCC, 2019)
The move towards digital communication environments over the past decades has changed the way consumers and brands interact with each other. The research combines key findings from earlier academic research with insights garnered from organisations working with and consumer perspectives about this technology. This book aims t o shed light on how brands can make strategic use of automated 1-2-1 communication, with a focus on conversational agents. in addition, it hightlights the importance of the communication professional in the implementation process and beyond. To assist communication professionals in this process the authors have created a checklist.
Keywords: consumentengedrag ; digitale veranderingen; merken ; communicatie